1997
DOI: 10.1210/en.138.9.4005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Prostaglandin Endoperoxide H Synthase 1 and 2 by Estradiol and Progesterone in Nonpregnant Ovine Myometrium and Endometrium in Vivo

Abstract: PG endoperoxide H synthase-2 (PGHS-2) messenger RNA (mRNA) and protein levels are increased dramatically in ovine myometrium and endometrium during both glucocorticoid-induced premature labor and spontaneous term labor. In this study, we examined estradiol and progesterone regulation in vivo of PGHS-1 and PGHS-2 expression at both mRNA and protein levels using a nonpregnant ovariectomized sheep model. We determined the differential distribution of PGHS-2 and PGHS-1 in ovine myometrium and endometrium with immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…We have repeatedly shown that COX1 is constitutively expressed in pregnant and nonpregnant uterine tissues (Zhang et al 1996, Wu et al 1999. COX2 is an inducible enzyme that responds to inflammatory cytokines, growth factors (Diaz et al 1992, Hempel et al 1994, and steroid hormones (Wu et al 1997(Wu et al 2004a(Wu et al , 2005b and is increased in intrauterine tissues, including the cervix during premature and spontaneous term labor (Wu et al 1999(Wu et al , 2004a(Wu et al , 2005a. Therefore, COX2 is the focal point of our present study.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…We have repeatedly shown that COX1 is constitutively expressed in pregnant and nonpregnant uterine tissues (Zhang et al 1996, Wu et al 1999. COX2 is an inducible enzyme that responds to inflammatory cytokines, growth factors (Diaz et al 1992, Hempel et al 1994, and steroid hormones (Wu et al 1997(Wu et al 2004a(Wu et al , 2005b and is increased in intrauterine tissues, including the cervix during premature and spontaneous term labor (Wu et al 1999(Wu et al , 2004a(Wu et al , 2005a. Therefore, COX2 is the focal point of our present study.…”
Section: Introductionmentioning
confidence: 61%
“…number: NP04) demonstrated in our previous study (Wu et al 1997). A rabbit polyclonal antibody for human mPTGES1 (Cayman Chemical Com, Ann Arbor, MI, USA) was used at 1:500 dilution and incubated at 4 8C for 20 h. A rabbit polyclonal antibody for bovine PTGFS kindly provided by Dr Watanabe (University of East Asia, Yamaguchi, Japan) was used at 1:500 dilution at 4 8C for 20 h. The primary antibodies used for immunocytochemistry were the same antibodies used for western analysis.…”
Section: Antibodies For Cox2 and Mptges1 And Ptgfs Used For Western Bmentioning
confidence: 73%
See 2 more Smart Citations
“…At term, the increased expression of Gq and PLC 1 and PLC 3 due to progesterone withdrawal and oestrogen increase respectively may underlie the enhancement of uterine responsiveness to uterotonic factors. In myometrium, the expression of many proteins including OTR, connexin-43, cyclo-oxygenase 2 and Gi2 protein was shown to be regulated at the transcriptional level by oestradiol (Larcher et al 1995, Lefebvre et al 1995, Cohen-Tannoudji et al 1995, Wu et al 1997). Whether or not oestradiol controls the expression of PLC 1 and PLC 3 at the transcriptional or post-transcriptional level remains to be determined.…”
Section: Discussionmentioning
confidence: 99%